Gender as a moderating element of customer satisfaction with electronic banking? An empirical study - Francisco Liébana-Cabanillas; Myriam Martínez-Fiestas; Francisco Rejón-Guardia; Francisco Mu\~noz-Leiva (The International Journal of Management Science and Information Technology (IJMSIT), 2012)
The importance of Electronic Banking as an alternative channel for marketing products and services, along with the associated cost savings, has brought about significant changes in the financial sector in recent years. Electronic Banking has become a differentiator among financial institutions, which has led to an attempt to increase customer satisfaction level by fulfilling their expectations. Accordingly, the goal of this paper is to identify the factors that influence the satisfaction level of Electronic Banking users in Spain, following a proposed behavioural model, in addition to determining the influence of the gender variable on our analysis, as a moderator in such relationships. The usefulness of this type of research for financial institutions lies in the support they provide in defining customer profiles. When compared to other similar online satisfaction survey studies, this paper is a pioneer in using empirical analysis to study the effects of gender on customer satisfaction in online banking.
Keywords: 650; Satisfaction; electronic banking; expectations; gender